Coronavirus Disease 2019: Associated Multiple Organ Damage. (21st June 2020) - Collange, Olivier; Tacquard, Charles; Delabranche, Xavier; Leonard-Lorant, Ian; Ohana, Mickaël; Onea, Mihaela; Anheim, Mathieu; Solis, Morgane; Sauer, Arnaud; Baloglu, Seyyid; Pessaux, Patrick; Ohlmann, Patrick; et al.
Abstract: A 56-year-old man presented a particularly severe and multisystemic case of coronavirus disease 2019 (COVID-19). In addition to the common lung and quite common pulmonary embolism and kidney injuries, he presented ocular and intestinal injuries that, to our knowledge, have not been described in COVID-19 patients. Although it is difficult to make pathophysiological hypotheses about a single case, the multiplicity of injured organs argues for a systemic response to pulmonary infection. A better understanding of physiopathology should feed the discussion about therapeutic options in this type of multifocal damage related to severe acute respiratory syndrome coronavirus 2. Abstract : This patient with severe COVID-19 presented damage to five different organs: lungs, kidneys, brain, eyes and gut were injured. The multiplicity of injured organs argues for a systemic response to SARS-CoV-2 infection. "